2012
DOI: 10.1016/j.dendro.2011.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Detecting changes in climate forcing on the fire regime of a North American mixed-pine forest: A case study of Seney National Wildlife Refuge, Upper Michigan

Abstract: a b s t r a c tThe study of forests dominated by red pine (Pinus resinosa Ait.), one of the few fire-resistant tree species of eastern North America, provides an opportunity to reconstruct long-term fire histories and examine the temporal dynamics of climate forcing upon forest fire regimes. We used a 300-year long spatially explicit dendrochronological reconstruction of the fire regime for Seney National Wildlife Refuge (SNWR, 38,531 ha), eastern Upper Michigan to: (1) identify fire size thresholds with stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…), or the identification of a threshold in fire sizes that would be indicative of climatically forced events (Drobyshev et al. ). Second, related to the methods applied in the analysis of fire–climate relationships, it is possible that the correlation between climate variables and fire occurrence is not constant in time, and this has indeed been demonstrated in North America (Swetnam and Betancourt , Hessl et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), or the identification of a threshold in fire sizes that would be indicative of climatically forced events (Drobyshev et al. ). Second, related to the methods applied in the analysis of fire–climate relationships, it is possible that the correlation between climate variables and fire occurrence is not constant in time, and this has indeed been demonstrated in North America (Swetnam and Betancourt , Hessl et al.…”
Section: Introductionmentioning
confidence: 99%
“…First, related to the fire data, it is important to distinguish local-scale controls from the influence of large-scale climatic controls (Kennedy and McKenzie 2010). This commonly requires widely distributed independent fire history reconstructions (Swetnam andBetancourt 1990, Trouet et al 2010), or the identification of a threshold in fire sizes that would be indicative of climatically forced events (Drobyshev et al 2012). Second, related to the methods applied in the analysis of fire-climate relationships, it is possible that the correlation between climate variables and fire occurrence is not constant in time, and this has indeed been demonstrated in North America (Swetnam and Betancourt 1998, Hessl et al 2004, Gavin et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Common fire years with the Seney National Wildlife Refuge area (roughly 200 km east of the HMR) include only 1754 and 1791 (Drobyshev et al, 2008(Drobyshev et al, , 2012. Dobryshev et al (2012) defined these as climate driven, major fire years, but the 1754 fire at HMR occurred at only one site (lower slope of a granite knob), scarring only 3% of all trees sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while the importance of humans in defining fire regimes has been established elsewhere (e.g., Guyette et al, 2002;Guyette, Spetich, & Stambaugh, 2006;Stambaugh, Guyette, & Marschall, 2013), there is little known about the importance of humans to the fire regime of the Lake States other than the spatial analysis of Loope and Anderton (1998). Fire history reconstruction studies have been conducted across the broad Great Lakes Region (Drobyshev, Goebel, Hix, Corace, & Semko-Duncan, 2008, Drobyshev, Goebel, Bergeron, & Corace, 2012Guyette & Dey 1995a, 1995bSands & Abrams 2011, among others), but we expect that the Huron Mountains present a distinct suite of topographic, climatic, and human factors that distinguish it from previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Climate and physiography were the major influences on stand-replacing and stand-maintaining fire in pre-settlement northern forests [9,10], whereas an early assessment of the role of fire in the virgin hardwood forests of northern Wisconsin concluded that historic fires "were not conflagrations of catastrophic proportions which destroyed the primeval forest and changed its climax formations into subclimax types of the present era, but rather periodic and ecologically normal events in the life of the forest…it has been and is, from a broad ecological viewpoint, a normal, beneficial and necessary factor in the perpetuation of virgin forest" [11]. Fire was also used by native peoples in portions of the Lake States region prior to EuroAmerican settlement and it is sometimes difficult to separate the importance of this anthropogenic fire from natural fire as a driver of forest dynamics [12][13][14].…”
Section: Percent Of Forest Areamentioning
confidence: 99%